Design for reusability and product reuse under radical innovation - Tamer Boyacı; Vedat Verter; Michael R. Galbreth (European School of Management and Technology (ESMT), 2016)
Many industries, including consumer electronics and telecommunications equipment, are characterized with short product life-cycles, constant technological innovations, rapid product introductions, and fast obsolescence. Firms in such industries need to make frequent design changes to incorporate innovations, and the effort to keep up with the rate of technological change often leaves little room for the consideration of product reuse. In this paper, we study the design for reusability and product reuse decisions in the presence of both a known rate of incremental innovations and a stochastic rate of radical innovations over time. We formulate this problem as a Markov Decision Process. Our steady-state results confirm the conventional wisdom that a higher probability of radical innovations would lead to reductions in the firm's investments in reusability as well as the amount of reuse the firm ends up doing. Interestingly, the design for reusability decreases much more slowly than the actual reuse. We identify some specific scenarios, however, where there is no tradeoff between the possibility of radical innovations and the firms reusability and reuse decisions. Based on over 425,000 problem instances generated over the entire range of model parameters, we also provide insights into the negative impact of radical innovations on firm profits, but show that the environmental impact of increased radical innovation is not necessarily negative. Our results also have several implications for policy makers seeking to encourage reuse.
urn:nbn:de:101:1-2016032215137
Keywords: 650; reusability; reuse; innovation; Markov decision process